Methodological aspects of improving the efficiency of workers in the extractive industry - A. V. Vaneev (Путеводитель предпринимателя, 2023)
The article considers various methodological approaches to assessing the labor efficiency of representatives of the mining industry. The labor efficiency of workers in the mining industry has different indicators, such as labor productivity, available resources, the degree of automation and other factors. But estimating efficiency in the extractive industry can be difficult due to a significant number of variables and the specifics of each specific sector of the industry.Labor productivity, as a key indicator of labor efficiency in the mining industry, can be measured, for example, by the amount of extracted resources (coal, oil, gas and other minerals) per employee or per labor shift, and the higher labor productivity, the more resources can be extracted with less labor costs.